Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ( 2x + 1 )2 + ( 2x - 1 )2 - ( 2x + 1 )( 2x - 1 )
= 4x2 + 4x + 1 + 4x2 - 4x + 1 - ( 4x2 - 1 )
= 8x2 + 2 - 4x2 + 1
= 4x2 + 3
b) Ta có :
2x3 - 3x2 + 6x - 9
= x2( 2x - 3 ) + 3( 2x - 3 )
= ( 2x - 3 )( x2 + 3 )
=> ( 2x3 - 3x2 + 6x - 9 ) : ( 2x - 3 ) = x2 + 3
1)
(x-3).(x+3) - (x+1)2
= x2 - 32 - x2 - 2x - 1
= - 2x - 10
2)
(2x - 1)2 - (x +2)2 - (2x - \(\dfrac{1}{2}\))2
= 4x2 - 4x +1 - x2 - 4x - 4 - 4x2 + 2x - \(\dfrac{1}{4}\)
= - x2 - 6x - \(\dfrac{13}{4}\)
= - ( x2 + 6x + \(\dfrac{13}{4}\) )
= - (x2 + 2.3x + 9 - \(\dfrac{23}{4}\))
= - (x + 3)2 + \(\dfrac{23}{4}\)
3)
(2x + 1)3 - (2x -1)3 - 24x2
= (2x -1 + 2)3 - (2x - 1)3 - 24x2
= (2x-1)3 + 3.(2x-1)2.2 + 3.(2x-1).22 + 23 - (2x - 1)3 - 24x2
= 6.(4x2 - 4x + 1) + 24x - 12 +8 - 24x2
= 24x2 - 24x + 6 +24x - 4 - 24x2
= 2
4)
(x-2)3 - (2x + 3)3 - 7.(1 - x)3
= x3 - 3.x2.2 + 3x.22 - 23 - 8x3 + 3.4x2.3 - 3.2x.32 + 33 - 7.(13-3x + 3x2 - x3)
= x3 - 3.x2.2 + 3x.22 - 23 - 8x3 + 3.4x2.3 - 3.2x.32 + 33 - 7 + 21x - 21x2 + 7x3
= x3 - 6x2 + 12x - 8 - 8x3 + 36x2 - 54x2 + 27 - 7 + 21x - 21x2 + 7x3
= - 45x2 + 33x + 12
= - 45(x2 - \(\dfrac{33}{45}x-\dfrac{4}{15}\))
= \(-45.\left(x^2-2.\dfrac{11}{30}.x+\dfrac{121}{900}-\dfrac{361}{900}\right)\)
= \(-45.\left(x-\dfrac{11}{30}\right)^2+\dfrac{361}{20}\)
a: \(=2x^2-x+5\)
b: \(=-\dfrac{3}{2}x^3+x^2-\dfrac{1}{2}x\)
c: \(=-x^3+\dfrac{3}{2}-2x\)
d: \(=-2x^2+4xy-6y^2\)
e: \(=\dfrac{3}{5}\left(x-y\right)^3-\dfrac{2}{5}\left(x-y\right)^2+\dfrac{3}{5}\)
B = (x-1)(2x+1) - (x2-2x-1)
B = 2x2+x-2x-1-x2-2x-1 = x2-3x-2
B = x2+x-4x-2 = x(x+1) - 4(x+1)
B = (x+1)(x-4)
\(A=2x\left(x-2\right)-x\left(2x-3\right)\\ =2x^2-4x-2x^2+3x\\ =-x\\ B=\left(x-1\right)\left(2x+1\right)-\left(x^2-2x-1\right)\\ =x\left(2x+1\right)-\left(2x+1\right)-x^2+2x+1\\ =2x^2+x-2x-1-x^2+2x+1\\ =x^2+x\\ C=\left(x+y\right)\left(x^2-xy+y^2\right)-x^3\\ =x\left(x^2-xy+y^2\right)+y\left(x^2-xy+y^2\right)-x^3\\ =x^3-x^2y+xy^2+x^2y-xy^2+y^3-x^3\\ =y^3\)
\(D=\left(12x-3\right)\left(x+4\right)-x\left(2x+7\right)\\ =x\left(12x-3\right)+4\left(12x-3\right)-2x^2-7x\\ =12x^2-3x+48x-12-2x^2-7x\\ =10x^2+38x-12\\ E=\left(2x+y\right)\left(4x^2-2xy+y^2\right)\\ =2x\left(4x^2-2xy+y^2\right)+y\left(4x^2-2xy+y^2\right)\\ =8x^3-4x^2y+2xy^2+4x^2y-2xy^2+y^3\\ =8x^3+y^3\)
a: \(=\left(x^4-x^3+2x^2+x+3\right)\left(x^2-2x+3\right)\)
\(=x^6-2x^5+3x^4-x^5+2x^4-3x^3+\left(2x^2+x+3\right)\left(x^2-2x+3\right)\)
\(=x^6-3x^5+5x^4-3x^3+2x^3-4x^3+6x^2+x^3-2x^2+3x+3\left(x^2-2x+3\right)\)
\(=x^6-3x^5+5x^4-6x^3+4x^2+3x+3x^2-6x+9\)
\(=x^6-3x^5+5x^4-6x^3+7x^2-3x+9\)
b: \(=\left(x^4+2x^3-2x^2+2x-3\right)\left(x^2-2x+3\right)\)
\(=x^6-2x^5+3x^4+2x^5-4x^4+6x^3-2x^4+4x^3-6x^2+\left(2x-3\right)\left(x^2-2x+3\right)\)
\(=x^6-3x^4+10x^3-6x^2+2x^3-4x^2+6x-3x^2+6x-9\)
\(=x^6-3x^4+12x^3-13x^2+12x-9\)
a) 2x(x-3)+5(x-3)=0
\(\Leftrightarrow\left(x-3\right)\left(2x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=0\\2x+5=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\frac{5}{2}\end{matrix}\right.\)
Vậy: phương trình đã cho có tập nghiệm S=\(\left\{3;-\frac{5}{2}\right\}\)
a,Ta có
x-3+x+3-(x\(^2\)+2x+1)=2x-x\(^2\)-2x-1=-x\(^2\)-1
b Ta có
4x^2-4x+1-(x^2+4x+4)-(4x^2-2x+1/4)=4x^2-4x+1-x^2-4x-4-4x^2+2x-1/4=-6x-x^2-13/4=(x+3)^2-23/4
c,Ta có
8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2=1+1=2
\(\left(2x^2-2x+3\right)\left(2x^2+2x-3\right)\)
\(=\left(2x^2\right)^2-\left(2x-3\right)^2\)
\(=4x^4-\left(4x^2-12x+9\right)\)
\(=4x^4-4x^2+12x-9\)